Mart-ool Kima Biche-oolovna (1936-2014) - ., . . (The New Research of Tuva, 2014)
February 18, 2014, on 78 year of life has suddenly died the national teacher of the Republic of Tuva, a specialistin the field of Tuvan linguistics, Methodist, Candidate of Pedagogy, Associate Professor, leading scientific employee of the Tuvan Institute of humanitarian studies Kima Biche-oolovna Mart-ool.
Keywords: obituary; TIGI; folklore